Production performance of Seurukan fish (Osteochilus sp.) with high density in recirculating system - Diansyah, Sufal; Febrina, Citra Dina; Islama, Dini; Samsuli, Said (Universitas Malikussaleh, 2024)
One of the local fish (native species) that is popular with the public and has quite good market prospects in Aceh is the seurukan fish (Osteochilus sp.). Seurukan fish cultivation technology with a recirculation system needs to be developed so that its potential can be utilized optimally. This research aims to evaluate production performance and determine the optimal stocking density for rearing seurukan fish (Osteochilus sp.) in a recirculation system. This research was conducted by experimental method. The experimental design used was a completely randomized design (CRD) with three treatments of stocking density and each treatment was repeated four times. The treatments are P1 (5 fish/m2), P2 (10 fish/m2), and P3 (15 fish/m2). The rearing period for Seurukan fish lasts for 50 days. The parameters tested during the research included biological parameters consisting of survival, absolute growth rate, feed conversion ratio, weight diversity coefficient, and water quality parameters including temperature, pH and dissolved oxygen. The results showed that the seurukan fish reared at different stocking densities using a recirculation system had a significant effect on the absolute growth rate and the coefficient of variation in weight. The best treatment in this study was 5 fish/m2, with a survival rate of 100%, an absolute growth rate of 0.04 g/head/day, a feed conversion ratio of 1.63, and a coefficient of variation of weight of 17.99%.Key words: production performance; seurukan fish; recirculation system; stocking density